EFL Teachers' Creativity and L2 Learners' Academic Attainment: The Moderating Role of Teaching Experience - Elnaz Zariholhosseini; Sajad Shafiee; Omid Tabatabaee (Journal of Modern Research in English Language Studies)
Creativity is an essential prerequisite for teaching, developing, and promoting a foreign language. Pupils show enthusiasm for learning a foreign language in a creative environment. The central goal of this research was, therefore, to inspect the variety between experienced and novice English-as-a-foreign (EFL) instructors regarding the interplay between their creativity and students' academic success. A closed-ended questionnaire was applied to inspect EFL experienced and novice teachers' promotion of creativity. Furthermore, the cumulative grade point average (CGPA) was applied as a substitute for measuring academic accomplishment. The questionnaire was distributed among 100 experienced teachers and 100 novice teachers in some branches of Gooyesh, Jahad Daneshgahi, and Sadr language institutes in Esfahan, Iran. In addition, their students' scores were gathered at the end of intended educational courses to calculate the classes' mean scores. Therefore, the data were analyzed descriptively and inferentially using frequency, percentage, Fisher's Z transformation formula, and mean. Besides, the Pearson correlation was utilized to gauge the connections between experienced and novice teachers' promotion of creativity and their students' academic achievements. The results confirmed the beneficial relationship between the creativity of experienced and novice instructors and students' academic performance. However, there was no significant disparity in the creativity levels of experienced and novice teachers